What constitutes a syndemic? Methods, contexts, and framing from 2019. Issue 4 (July 2020) - Mendenhall, Emily; Singer, Merrill
Abstract : Purpose of review: The purpose of this review is to describe what methods were used for 60 articles on HIV syndemics in 2019, where they took place, what syndemic clusters emerged, and why this matters. Recent findings: Most articles published in 2019 used regression analyses, and fewer used higher level modeling techniques, frequencies and descriptive, longitudinal cohort study, and social network analysis. Some employed ethnography, qualitative interviews, or were simply reviews. Most syndemic co-factors were substance abuse, risky sexual behavior, depression, intimate partner violence, stigma, sexually transmitted infections, and trauma and non-communicable diseases. Half of the studies were conducted in the United States and mostly in urban areas. Other contexts were Canada, Kenya, Uganda, Liberia, Nigeria, South Africa, and Botswana, Jamaica, Dominican Republic, India, Indonesia, China, Peru, and Romania. Summary: Most recommendations suggested that people living with HIV need interventions that address other factors situated within their life, such as their mental health, social stigma, experiences of trauma and intimate partner violence, and social stigma and sexual risk taking. Many took an intersectoral approach and emphasized the need to consider the various factors that shape experiences with HIV, from sex, sexuality, class, race and ethnicity, and past trauma.